RANCANGAN AWAL PENGEMBANGAN BAHAN AJAR BAHASA SENTANI - Esther Rita Embram (Balai Bahasa Provinsi Papua, 2019)
Sentani language is the one of local languages in Papua which is endangered.Therefore, efforts are needed to slow the symptoms. One of them by teaching thelanguage of Sentani to children at an early age. So far there has been no research ineducation and teaching that supports Sentani language defense. This is marked by theabsence of teaching materials Sentani language. Teachers do not have guidance inteaching the Sentani language so that the existence of teaching materials is importantso that the learning of Sentani language is more structured, effective, and successful.This research is based on a general approach of research and development or researchdevelopment. The theory used is the theory of principles and procedures development ofteaching materials with language learning approach. Data collection was done by directobservation, interview technique, questionnaire of requirement analysis, and technicalnote. The result of data analysis is the early model of Sentani language teaching bookfor beginner which consists of unit one greeting theme (Foi Moi). Unit two familytheme (Imea). Unit three healthy body theme (Uga foisele). Unit four food theme(Ramang). Unit five numbers theme (Me bheai). Unit six color theme (Rahe bhu).